Tinjauan Yuridis Terhadap Penutupan Jalan Sementara untuk Kepentingan Pribadi - Anak Agung Ayu Angelita Thandayuthavani (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
Roads are one of the facilities in the field of infrastructure whose main function is as a means of land transportation access. However, the existence of these facilities is currently found to be irregularities in the main function of the road, namely in the form of the closure of the road for personal interests. Because of this event, it will result in disruption of road function if it is not strictly regulated. Based on these problems, this study is intended as a juridical review of the legal umbrella that can be used in these problems. The method used is a normative legal method with a legislative approach which is then analyzed qualitatively. The result of this study is that road closures are allowed based on the LLAJ Law and the National Police Chief Regulation 10/2012 by submitting an application and attaching several requirements. Then as a result of the permission to close the road, it will give rise to an obligation along with legal sanctions.